A cation-exchange approach to tunable magnetic intercalation superlattices - Zhou, Jingxuan; Zhou, Jingyuan; Wan, Zhong; Qian, Qi; Ren, Huaying; Yan, Xingxu; Zhou, Boxuan; Zhang, Ao; Pan, Xiaoqing; Fang, Wuzhang; Ping, Yuan; Sofer, Zdenek; et al. (Nature, 2025)
Tailoring magnetic ordering in solid-state materials is essential for emerging spintronics1,2. However, substitutional lattice doping in magnetic semiconductors is often constrained by the low solubility of magnetic elements3-5, limiting the maximum achievable doping concentration (for example, less than 5%) and ferromagnetic ordering temperature6. The intercalation of magnetic elements in layered two-dimensional atomic crystals (2DACs) without breaking in-plane covalent bonds offers an alternative approach to incorporate a much higher concentration of magnetic atoms (for example, up to 50%) beyond the typical solubility limit. However, commonly used chemical and electrochemical intercalation methods are largely confined to a few isolated examples so far. Here we report a general two-step intercalation and cation-exchange strategy to produce a library of highly ordered magnetic intercalation superlattices (MISLs) with tunable magnetic ordering. Monovalent transition-metal cations Cu+ and Ag+, divalent magnetic cations Mn2+, Fe2+, Co2+ and Ni2+, and trivalent rare-earth cations Eu3+ and Gd3+ have been successfully incorporated into group-VIB 2DACs, including MoS2, MoSe2, MoTe2, WS2, WSe2 and WTe2, and group-IVB, -VB, -IIIA, -IVA and -VA 2DACs, including TiS2, NbS2, NbSe2, TaS2, In2Se3, SnSe2, Bi2Se3 and Bi2Te3. We show that these MISLs can be prepared with tunable concentrations of magnetic intercalants, enabling tailored magnetic ordering across a diverse array of functional 2DACs, including semiconductors, topological insulators, and superconductors. This work establishes a versatile material platform for both fundamental investigations and spintronics applications.